2019
DOI: 10.1158/1535-7163.mct-18-1346
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Candidate Druggable Targets in Canine Cancer Cell Lines Using Whole-Exome Sequencing

Abstract: Cancer cell culture has been a backbone in cancer research, in which analysis of human cell line mutational profiles often correlates with oncogene addiction and drug sensitivity. We have conducted whole-exome sequence analyses on 33 canine cancer cell lines from 10 cancer types to identify somatic variants that contribute to pathogenesis and therapeutic sensitivity. A total of 66,344 somatic variants were identified. Mutational load ranged from 15.79 to 129.37 per Mb, and 13.2% of variants were located in pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 58 publications
2
50
1
Order By: Relevance
“…Although anticancer agents originally developed to treat human cancers may be applied to dogs, little evidence has been given in terms of their therapeutic efficacy, especially in relation to cost effectiveness. Recently, a study of drug sensitivity showed trametinib (a MEK1/2 inhibitor) to be effective in canine cancer cell lines 46 , and we expect more lines of evidence will accumulate on trans-species use of more drugs of these kinds. In spite of a concern regarding the discordance between animal and human in drug efficacy and toxicities 47 , treatment of canine cancer may benefit from the development of novel human cancer drugs that target shared oncogenic mutations (e.g., alpelisib for metastatic breast cancer with PIK3CA mutations 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although anticancer agents originally developed to treat human cancers may be applied to dogs, little evidence has been given in terms of their therapeutic efficacy, especially in relation to cost effectiveness. Recently, a study of drug sensitivity showed trametinib (a MEK1/2 inhibitor) to be effective in canine cancer cell lines 46 , and we expect more lines of evidence will accumulate on trans-species use of more drugs of these kinds. In spite of a concern regarding the discordance between animal and human in drug efficacy and toxicities 47 , treatment of canine cancer may benefit from the development of novel human cancer drugs that target shared oncogenic mutations (e.g., alpelisib for metastatic breast cancer with PIK3CA mutations 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the functional enrichment analysis uncovered the link between dcEFs associated genes and cancer-related pathways, however, detail mechanisms were still needed. To further investigate the validity of this link, cBioportal (an online web-based integrated data mining system) was used to explore the genetic alteration of genes associated with lung cancer 24,42,43 . www.nature.com/scientificreports www.nature.com/scientificreports/ Among the six tumor types we used as dataset [44][45][46][47][48][49] , the expression levels of these hub genes varied from 0.2% to 19% (Fig.…”
Section: Mining Genetic Alterations Connected With Lung Cancer-associmentioning
confidence: 99%
“…WES became recognized as a more efficient means for genome resequencing in 2007 and has increasingly been used to help diagnose patients with rare and genetic diseases 3,4 . By selectively sequencing all protein-coding regions to great depth, WES is a dependable method to find exome variants 5 . Most often WES is a powerful approach to study Mendelian inherited diseases because highly functional impact variants rarely appear in the healthy populations 6 7 .…”
Section: Introductionmentioning
confidence: 99%